Effect of nicotine 6 mg gum on urges to smoke, a randomized clinical trial - Anna Hansson; Thomas Rasmussen; Roland Perfekt; Elin Hall; Holger Kraiczi (BMC, 2019)
Abstract Background Ability to manage urges to smoke is fundamental to maximizing the chances of success in smoking cessation. Previous studies have linked a higher dose of nicotine in nicotine replacement therapy to a higher success rate for smoking cessation. Thus, this study was performed to compare relief of urges to smoke, up until 5 h following treatment with a new 6 mg nicotine gum versus currently marketed 4 mg nicotine gum. Methods This was a randomized crossover clinical study. Following 12 h of abstinence from smoking, either one 6 mg or one 4 mg nicotine gum was given to 240 healthy adult smokers. Thereafter, urges to smoke were scored on a 100 mm Visual Analogue Scale repeatedly over 5 h. Results The reductions in urges to smoke over the first 1 and 3 h after administration were statistically significantly greater with 6 mg than 4 mg gum, (p < 0.005). A 50% reduction in perceived urges to smoke was reached in 9.4 min with 6 mg gum compared to 16.2 min with 4 mg gum (median values). The median duration of a 50% or more reduction in VAS urges to smoke score was 111 min with the 6 mg gum, versus 74 min for the 4 mg gum. Conclusion This study provides evidence that the 6 mg nicotine gum provided a greater reduction, faster and longer relief of urges to smoke than the 4 mg nicotine gum. Trial registration EudraCT Number: 2010-023268-42. Study was first entered in EudraCT 2011-02-23.